Miradas sobre el manglar. Saberes tradicionales y conocimientos científicos (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
This short essay, with accompanying photography, highlights the importance of establishing relationships between traditional and scientific forms of knowledge, topics that have generated debated and extreme opinions among social scientists. The proposals of this work are based upon contextualized field experiences in the municipality of El Realejo in western Nicaragua, where the extraction of black shellfish was studied in the mangrove ecosystem. The influence and primary role of traditional knowledge was observed in the practices used to regenerate the shellfish species, in absence of environmental regulations. In such situations, it is opportune to focus on the strengths of traditional knowledge in a system with balanced goals of resource use, quality of life and wetland health.
Keywords: Traditional knowledge, scientific knowledge, experiences, anthropology of knowledge